Media Pembelajaran Online : Pemanfaatan Kahoot Dalam Kegiatan Evaluasi Pembelajaran Online - Aniisah, Amiirah; Kamilah, Athia Nur; Syam, Aldo Redho (International Journal of Learning and Education, 2025)
This study aims to map trends, thematic evolution, and gaps in the scientific literature concerning online learning evaluation, specifically the utilization of gamified platforms such as Kahoot. This systematic review employs a quantitative bibliometric approach, analyzing articles from the Google Scholar database for the period 2018–2022. The analysis was conducted using the Publish or Perish application for data collection and VOSviewer for network, overlay, and density visualization to identify citation patterns and conceptual clusters. The results indicate a significant surge in publications in 2021, driven by the need for emergency evaluation during the COVID-19 pandemic. The discussion reveals that the literature tends to focus on pragmatic aspects and tool adoption, with limited conceptual linkages to deeper theoretical constructs such as assessment as learning and self-regulation. The key finding highlights the need to shift from "how-to" facilitation-focused research toward exploring how technology can transform assessment practices to support deeper learning. The implication is that future research should investigate intentionally designed, pedagogically sound online evaluations that leverage the unique affordances of digital and game-based tools to foster 21st-century competencies, as well as examine their long-term impact and causal pathways beyond the crisis context.